2021
DOI: 10.4018/joeuc.287571
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Patients' Satisfaction With Doctors in Online Medical Communities

Abstract: Online medical communities have revolutionized the way patients obtain medical-related information and services. Investigating what factors might influence patients’ satisfaction with doctors and predicting their satisfaction can help patients narrow down their choices and increase their loyalty towards online medical communities. Considering the imbalanced feature of dataset collected from Good Doctor, we integrated XGBoost and SMOTE algorithm to examine what factors and these factors can be used to predict p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Chatterjee et al (2021) employed XGBoost for computing product reviews and attained best outcomes with forecasting user satisfaction among other classifiers (e.g., random forest). In addition, Xu et al (2022) applied XGBoost for analyzing users' comments towards doctors and achieved advanced results in predicting patients' satisfaction. Hew et al (2020) revealed that examining online reviews with GBM has a great power (F1 score: 0.8375) in forecasting user satisfaction with online learnings.…”
Section: User Satisfaction With Mobile Healthcare Servicesmentioning
confidence: 99%
“…Chatterjee et al (2021) employed XGBoost for computing product reviews and attained best outcomes with forecasting user satisfaction among other classifiers (e.g., random forest). In addition, Xu et al (2022) applied XGBoost for analyzing users' comments towards doctors and achieved advanced results in predicting patients' satisfaction. Hew et al (2020) revealed that examining online reviews with GBM has a great power (F1 score: 0.8375) in forecasting user satisfaction with online learnings.…”
Section: User Satisfaction With Mobile Healthcare Servicesmentioning
confidence: 99%
“…Users share knowledge, and member exchanges and other activities occur in the community, about health-or treatment-related issues (Wu & Lu, 2016). In contrast with traditional doctor-centered medical and health service model, OHCs provide users with an open network service platform for experience sharing, information exchange, and asking questions on health care-related issues (Xu, Wu, & Chen, 2022). OHCs with professional doctors also reduce the cost to patients seeking health information and medical assistance, and provide hospitals with opportunities to expand their market.…”
Section: Online Health Communities and Continuous Use Intention (Cui)mentioning
confidence: 99%